The Significance of Foreign Experiences In Enhancing Individual Ecological Activity And Their Relevance In The Context of Global Climate Change - Alimjanov, Farhod (Jurnal Lingkungan Kebumian Indonesia, 2025)
The most effective way to mitigate the negative impact of social actors on nature and the environment is to foster individual ecological engagement. Ecological engagement at the individual level reflects not only the actions of a single social actor but also embodies the efforts of every society and all its members toward achieving ecological sustainability. Examining the experiences of foreign countries in enhancing individual ecological engagement and understanding their principles effectively nurtures a sense of responsibility for ecosystem protection among students. This article discusses international practices to promote individual ecological engagement and their importance in the context of global climate change.